Noxious weed monitoring at the U.S. Air Force Academy: year 9 results - Rondeau, Renée, author; Lavender-Greenwell, Amy, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
This report includes a summary of the results of the past nine years of population monitoring of targeted noxious weeds at the U.S. Air Force Academy ("the Academy"), emphasizing changes that were observed between 2012 and 2013.
Prepared for: U.S. Air force Academy Department of Natural Resources.
April 2014.
Keywords: Colorado; noxious weeds; weed control; vegetation surveys